2016
DOI: 10.1002/jqs.2908
|View full text |Cite
|
Sign up to set email alerts
|

A refined paleotemperature calibration for New Zealand limnic environments using differentiation of branched glycerol dialkyl glycerol tetraether (brGDGT) sources

Abstract: Branched glycerol dialkyl glycerol tetraethers (brGDGTs) were abundant in surface sediments of freshwater lakes and in catchment soils at altitudes from 10 to 2020 m in New Zealand. Significant differences in brGDGT compositions between lake sediments and soils indicate sources from separate microbial habitats. An expanded modern calibration dataset comprising 33 lakes has enabled a revised calibration function for determining past mean annual air temperature (MAT) from brGDGTs in New Zealand lake sediments: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 62 publications
(180 reference statements)
1
16
0
Order By: Relevance
“…To analyse the GDGT content, aliquots of the polar fractions were dissolved in n-hexane:2-propanol (99 : 1; v/v) and passed through a 0.4 µm polytetrafluoroethylene filter. Analysis of GDGTs was performed using an Alliance 2695 (Waters, UK) high-performance liquid chromatograph coupled to a ZQ (Micromass, UK) single quadrupole mass spectrometer (MS) as detailed in Zink et al (2016) following the analytical protocols of Hopmans et al (2000) and Liu et al (2012). Isoprenoid and branched GDGTs were detected using single ion recording of their protonated molecules [M+H] + as outlined in Schouten et al (2013a).…”
Section: Biomarkersmentioning
confidence: 99%
“…To analyse the GDGT content, aliquots of the polar fractions were dissolved in n-hexane:2-propanol (99 : 1; v/v) and passed through a 0.4 µm polytetrafluoroethylene filter. Analysis of GDGTs was performed using an Alliance 2695 (Waters, UK) high-performance liquid chromatograph coupled to a ZQ (Micromass, UK) single quadrupole mass spectrometer (MS) as detailed in Zink et al (2016) following the analytical protocols of Hopmans et al (2000) and Liu et al (2012). Isoprenoid and branched GDGTs were detected using single ion recording of their protonated molecules [M+H] + as outlined in Schouten et al (2013a).…”
Section: Biomarkersmentioning
confidence: 99%
“…They defined new indices and established new calibrations. Lake sediment studies have involved the development of specific calibrations (Bendle et al, 2010;Blaga et al, 2010;Tierney et al, 2010;Sun et al, 2011;Zink et al, 2016;Russell et al, 2018). Most of these studies demonstrated that in situ production in the water column or in the sediment could occur, potentially biasing the results obtained (Tierney and Russell, 2009;Loomis et al, 2011;Tierney et al, 2012;Wang et al, 2012a;Buckles et al, 2014aBuckles et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…To analyse the GDGT content, aliquots of the polar fractions were dissolved in n-hexane:2-propanol (99 : 1; v/v) and passed through a 0.4 µm polytetrafluoroethylene filter. Analysis of GDGTs was performed using an Alliance 2695 (Waters, UK) high-performance liquid chromatograph coupled to a ZQ (Micromass, UK) single quadrupole mass spectrometer (MS) as detailed in Zink et al (2016) following the analytical protocols of Hopmans et al (2000) and Liu et al (2012). Isoprenoid and branched GDGTs were detected using single ion recording of their protonated molecules [M+H] + as outlined in Schouten et al (2013a).…”
Section: Biomarkersmentioning
confidence: 99%